2015
DOI: 10.2340/16501977-1922
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive devices in young people with upper limb reduction deficiencies: Use and satisfaction

Abstract: Young people with upper limb reduction deficiencies are satisfied and socially well-adjusted with adaptive devices. Adaptive devices are good alternatives to prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Neither of the statements is supported by evidence. Østlie et al 27 ( n = 224) and Vasluian et al 6 ( n = 218) report that people with an upper limb deficiency often prefer the use of both the unaffected and the affected body parts instead of prostheses. For some ADLs, such as tying shoelaces, external help is preferred.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neither of the statements is supported by evidence. Østlie et al 27 ( n = 224) and Vasluian et al 6 ( n = 218) report that people with an upper limb deficiency often prefer the use of both the unaffected and the affected body parts instead of prostheses. For some ADLs, such as tying shoelaces, external help is preferred.…”
Section: Resultsmentioning
confidence: 99%
“… 41 The major improvement of the use of prosthetic tools is found in activities where bimanual activity is obligatory, such as lifting barbells or playing the violin. 6 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…People with upper limb reduction deficiencies (ULRD) for example will have difficulties to use the zipper. In a study conducted by Vasluian et al, more than 50% of the youngsters with ULRD reported having problems to perform their daily life self-care activity of dressing and undressing and tying their shoelaces [6]. This group of people who live with only one arm, or did not have any arm, will have major consequences to execute their daily task.…”
Section: Introductionmentioning
confidence: 99%